(untitled) (Research, Society and Development, 2022)
Objective: To establish the relationship between mortality and cardiovascular risk factors of patients with acute myocardial infarction knowing the region of Brazil with the highest number of deaths from AMI and the highest mortality rate, elucidating the risk factor with greater epidemiological agreement with mortality from AMI. Methodology: A bibliographic research was carried out using the computational tool Publish or Perish using the descriptors "ACUTE MYOCARDIAL INFARCTION", "RISK FACTORS", "PREVALENCE" "PROGNOSIS, after exclusion, 16 articles were systematically reviewed in the integra. Subsequently, an ecological research was conducted on mortality from AMI by region of Brazil in the last 10 years, using the variables: gender, color/race, region and age group. Results: A total of 122,012 deaths from AMI were recorded, with the total value increasing year by year. About 55.96% of the deaths were male. Women accounted for 44.03% of deaths. The region with the highest number of deaths was the Southeast, but the mortality rate was higher in the Northeast. The risk factor that most followed mortality by region was Diabetes Mellitus. Conclusion: Mortality from AMI has been increasing in most Brazilian regions and is strongly associated with the prevalence of risk factors in the population studied. Among the various approaches for the treatment of coronary atherosclerosis, the control of these factors, especially Diabetes, should receive a primary focus, since it is thus possible to postpone the onset of the disease. Conclusión: La mortalidad por IAM viene aumentando en la mayoría de las regiones brasileñas y está fuertemente asociada con la prevalencia de factores de riesgo en la población estudiada. Entre los diversos enfoques para el tratamiento de la aterosclerosis coronaria, el control de estos factores, especialmente la diabetes, debe recibir un enfoque principal, ya que por lo tanto es posible posponer la aparición de la enfermedad.